PENERAPAN TEKNOLOGI PENGEMASAN GULA SEMUT UNTUK PENINGKATAN PENDAPATAN MASYARAKAT DI DUSUN LINGKUNGAN KECAMATAN SUNGAYANG KABUPATEN TANAH DATAR - Dwi Yulia; Adrianis Adrianis (Jurnal Hilirisasi IPTEKS, 2021)
Ant sugar is made from sap water from the sap tree, which is widely found in highland areas, hilly hills, or mountains with cold temperatures. The sap tree is widely available in the Tanah Datar Regency, precisely in the Sungayang Nagari Andaleh Baruh Bukit District in Lingkungan village. The process of making ant sugar in this environmental area still uses traditional processing methods and equipment. This is due to various factors, including limited capital, untrained human resources for producing ant sugar, and the high cost of sophisticated equipment. Simple processing and minimal tools do not guarantee hygiene and less effective packaging. This activity aims to improve the knowledge and skills of ant sugar makers in the Environmental Hamlet about packaging technology to improve the quality of ant sugar. The method in this activity is through socialization about the equipment used hygienically, demonstrations on the use of goods hygienically, and demonstrations of packaging methods that are more modern than they do to increase immunity during the Covid-19 pandemic. The results obtained were an increase in the knowledge and skills of ant sugar makers in the Environmental Hamlet about hygienic, modern, and selling-value packaging technology to increase the income of ant sugar farmers. It is improving the quality and sales of ant sugar farmers and ensuring product cleanliness in improving health during the Covid-19 pandemic.